FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL BELAJAR IPS EKONOMI KELAS VII DI SMP N 1 BAYANG - Rahmadani, Anisa; Wahyuni, Sri; Susanti, S.Pd, Desi (Pendidikan Ekonomi, 2014)
ABSTRACT This study aims to determine: 1) How much influence student learning motivation on learning outcomes of students in social studies economics at SMP N 1 Bayang. 2) How much influence method learning on student learning outcomes in social studies economics at SMP N 1 Bayang. 3) How big is the influence of learning media on outcomes of students learning in social studies economics at SMP N 1 Bayang. 4) How much motivation influence, methods and instructional media on outcomes economic learning student IPS in SMP N 1 Bayang.This type of research is descriptive quantitative. This research was carried out for 1 week. The population of this study was student of class VII in SMP N 1 Bayang totaling 105 people. This research sampling technique is proportional random sampling technique which means the technique used to obtain samples at each sampling unit which samples were taken every class conducted lottery or random. This type of data is the primary data (ie, questionnaires) and secondary data. Data analysis was descriptive and inferential analysis through hypothesis testing using the F test and t test with α = 0.05 The results of this study indicate that: 1) there is a significant effect of learning motivation on learning outcomes of IPS Economy Grade VII in SMP N 1 Bayang, significance of 0.002, 2) there are significant between the learning method on learning outcomes Economics social studies class VII in SMP N 1 Bayang, then the significance of 0.000, 3) there is a significant relationship between instructional media on the learning results of class VII social studies Economics The SMP N 1 Bayang, significant at 0.024, 4) motivation, methods of learning and instructional media have a significant effect together on learning outcomes in SMPN 1 Bayang, with a significance level of 0.130.In this study the authors suggested that students are more motivated to learn well and the learning methods and instructional media should be used by teachers to improve student learning outcomes in the direction of better